"It's Complicated"—Sex Differences in Perceptions of Cross-Sex Friendships. Issue 2 (3rd March 2016) - Hart, William; Adams, John; Tullett, Alexa
ABSTRACT: Surprisingly, little is known about how a person's sex relates to beliefs about cross-sex friendships. In this study, participants completed a survey in which they provided separate estimates for the percentage of cross-sex friendships that contained secret "female-on-male" and "male-on female" sexual interest, indicated their optimism in the idea that males and females could be "just friends, " and reported their comfort with their partner forming a cross-sex friendship. Males were just as optimistic as females about the possibility and indicated similar levels of discomfort in response to imagining their partner entering into a cross-sex friendship. Furthermore, males did not provide higher estimates of sexual interest in cross-sex friendships compared to females. Instead, a more nuanced pattern emerged. Males (vs. females) provided higher estimates of male-to-female sexual interest, but females (vs. males) provided higher estimates of female-to-male sexual interest.